Activating ERBB2/HER2 mutations indicate susceptibility to pan-HER inhibitors in Lynch and Lynch-like colorectal cancer. Issue 8 (28th April 2015) - Kloth, Michael; Ruesseler, Vanessa; Engel, Christoph; Koenig, Katharina; Peifer, Martin; Mariotti, Erika; Kuenstlinger, Helen; Florin, Alexandra; Rommerscheidt-Fuss, Ursula; Koitzsch, Ulrike; Wodtke, Claudia; Ueckeroth, Frank; et al.
Abstract : Objective: Microsatellite instability (MSI) is detected in approximately 15% of all colorectal cancers (CRC) and virtually in all cases with Lynch syndrome. The MSI phenotype is caused by dysfunctional mismatch repair (MMR) and leads to accumulation of DNA replication errors. Sporadic MSI CRC often harbours BRAF V600E ; however, no consistent data exist regarding targeted treatment approaches in BRAF wt MSI CRC. Design: Mutations and quantitative MSI were analysed by deep sequencing in 196 formalin fixed paraffin embedded (FFPE) specimens comprising Lynch and Lynch-like CRCs from the German Hereditary Nonpolyposis Colorectal Cancer registry. Functional relevance of recurrent ERBB2/HER2 mutations was investigated in CRC cell lines using reversible and irreversible HER-targeting inhibitors, EGFR-directed antibody cetuximab, HER2-directed antibody trastuzumab and siRNA-mediated ERBB2/HER2 knockdown. Results: Quantification of nucleotide loss in non-coding mononucleotide repeats distinguished microsatellite status with very high accuracy (area under curve=0.9998) and demonstrated progressive losses with deeper invasion of MMR-deficient colorectal neoplasms (p=0.008). Characterisation of BRAF wt MSI CRC revealed hot-spot mutations in well-known oncogenic drivers, including KRAS (38.7%), PIK3CA (36.5%), and ERBB2 (15.0%). L755S and V842I substitutions in ERBB2 were highly recurrent. Functional analyses in ERBB2-mutated MSI CRC cell lines revealed a differential response to HER-targeting compounds and superiority of irreversible pan-HER inhibitors. Conclusions: We developed a high-throughput deep sequencing approach for concomitant MSI and mutational analyses in FFPE specimens. We provided novel insights into clinically relevant alterations in MSI CRC and a rationale for targeting ERBB2/HER2 mutations in Lynch and Lynch-like CRC.